How do you find the derivative of #3x^2-5x+2# using the limit definition?

Answer 1

# f'(x)=6x-5 #

By definition of the derivative # f'(x)=lim_(h rarr 0) ( f(x+h)-f(x) ) / h # So with # f(x) = 3x^2 - 5x + 2 # we have;
# f'(x)=lim_(h rarr 0) ( {3(x+h)^2-5(x+h)+2 } - {3x^2 - 5x + 2 } ) / h # # :. f'(x)=lim_(h rarr 0) ( {3(x^2+2hx+h^2)-5(x+h)+2 } - {3x^2 - 5x + 2 } ) / h # # :. f'(x)=lim_(h rarr 0) ( {3x^2+6hx+3h^2-5x-5h+2 - 3x^2 + 5x - 2 } ) / h #
# :. f'(x)=lim_(h rarr 0) ( {6hx+3h^2-5h } ) / h #
# :. f'(x)=lim_(h rarr 0) ( 6x+3h-5 ) #
# :. f'(x)=6x-5 # # :. f'(x)=6x-5 #
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

To find the derivative of (3x^2 - 5x + 2) using the limit definition, you would use the formula:

[ f'(x) = \lim_{{h \to 0}} \frac{{f(x + h) - f(x)}}{h} ]

where (f(x) = 3x^2 - 5x + 2).

Substitute (f(x + h)) and (f(x)) into the formula:

[ f(x + h) = 3(x + h)^2 - 5(x + h) + 2 ] [ f(x) = 3x^2 - 5x + 2 ]

Expand (f(x + h)) and simplify:

[ f(x + h) = 3(x^2 + 2hx + h^2) - 5x - 5h + 2 ] [ f(x + h) = 3x^2 + 6hx + 3h^2 - 5x - 5h + 2 ]

Substitute (f(x + h)) and (f(x)) back into the formula and simplify:

[ f'(x) = \lim_{{h \to 0}} \frac{{(3x^2 + 6hx + 3h^2 - 5x - 5h + 2) - (3x^2 - 5x + 2)}}{h} ] [ f'(x) = \lim_{{h \to 0}} \frac{{6hx + 3h^2 - 5h}}{h} ]

Factor out (h) from the numerator:

[ f'(x) = \lim_{{h \to 0}} \frac{{h(6x + 3h - 5)}}{h} ]

Cancel out the (h) terms:

[ f'(x) = \lim_{{h \to 0}} (6x + 3h - 5) ]

Substitute (h = 0):

[ f'(x) = 6x - 5 ]

Therefore, the derivative of (3x^2 - 5x + 2) with respect to (x) using the limit definition is (6x - 5).

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7